2020
DOI: 10.1088/1402-4896/abd202
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer and differential thermal analysis studies of iron alkali lead-phosphate glasses

Abstract: This work reports on the effect of the increment of Fe2O3 in a network of phosphate glasses involving Al2O3, Na2O and PbO by DTA and Mössbauer techniques. The analysis of Mössbauer suggests oxidation of Fe2+ ions in the distorted bipyramidal to Fe3+ in the same site. This procedure creates non-bridging oxygens joined with Fe2+ octa that weakens the phosphate network whenever the Fe2O3 content increases. The thermal parameters of the phosphate network will be affected by this weakness. Thus, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…PbO is a metallic oxide that expands the chemical stability of phosphate glass due to the number of factors since (Pb 2+ ) ions improve its chemical stability via formed "P-O-Pb" bonding. PbO enhances the moistness resistance of the formed glass [8]. ________________________________________________ Egypt.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PbO is a metallic oxide that expands the chemical stability of phosphate glass due to the number of factors since (Pb 2+ ) ions improve its chemical stability via formed "P-O-Pb" bonding. PbO enhances the moistness resistance of the formed glass [8]. ________________________________________________ Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…And according to the previous mentioned characteristics, it is found that Glasses made of "PbO-ZnO-P2O5" have improved chemical and physical endurance while keeping low glass conversion and softening points. [8]. Furthermore, the production and classification of ternary "PbO-ZnO-P2O5" glasses offer glass-tometal sealant possibility in nuclear reactor windows, isotope handling facilities, and any other increased irradiation region where dramatic irradiation mitigation is needed [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation